Eaarth : making a life on a tough new planet - McKibben, Bill (Time Books, 2010)
McKibben's earliest warnings about global warming went largely unheeded. In this book, he argues that we can meet the challenges of a new "Eaarth"--still recognizable but suddenly and violently out of balance--by building the kind of societies and economies that can hunker down, concentrate on essentials, and create the type of community that will allow us to weather trouble on an unprecedented scale.